Bioedutainment-Based Jenga Board Game: A Learning Media Development for Human Digestive System Material - Ningsih, Rahmi Dwi; Jamilah, Jamilah; Zulkarnaim, Zulkarnaim; Rijal, Muhammad (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
The research aimed to determine the characteristics, validity, and practicality of the bioedutainment-based Jenga board game for teaching the digestive system topic to eighth-grade students of SMPN Sinjai. This research employed the research and development method with the ADDIE development model, involving 25 eighth-grade students as subjects. The ADDIE development model comprises five stages: analyze, design, develop, implement, and evaluate. The research instruments were questionnaires to obtain data on practicality and test items to obtain data on effectiveness. The analysis showed that the media had an attractive design and received a 100% validation rating. It was determined as highly practical by students and educators. The score of effectiveness was 77, reaching 96% completeness. Thus, the bioedutainment-based Jenga board game is valid, practical, and effective for classroom learning.ABSTRAK: Penelitian ini bertujuan untuk mengetahui karakteristik, validitas, dan kepraktisan media permainan papan Jenga berbasis bioedutainment untuk pembelajaran sistem pencernaan pada siswa kelas VIII SMPN Sinjai. Penelitian ini menggunakan metode penelitian dan pengembangan berdasarkan model pengembangan ADDIE, dengan melibatkan 25 siswa kelas VIII sebagai subjek. Model pengembangan ADDIE terdiri dari lima tahapan yaitu menganalisis, merancang, mengembangkan, menerapkan, dan mengevaluasi. Instrumen penelitian berupa angket untuk data kepraktisan, serta soal tes untuk data keefektifan. Hasil penelitian menunjukkan bahwa media tersebut memiliki desain yang menarik dan mendapat nilai validitas 100%. Itu dinilai sangat praktis oleh siswa dan pendidik. Data keefektifan menunjukkan skor 77, mencapai ketuntasan 96%. Dengan demikian, media permainan papan Jenga berbasis bioedutainment valid, praktis, dan efektif untuk pembelajaran di kelas.